The Impact of Aging in Acute Respiratory Distress Syndrome: A Clinical and Mechanistic Overview - Brown, Ryan; McKelvey, Michael C.; Ryan, Sinéad; Creane, Shannice; Linden, Dermot; Kidney, Joseph C.; McAuley, Daniel F.; Taggart, Clifford C.; Weldon, Sinéad (Frontiers in Medicine, 2020)
Acute respiratory distress syndrome (ARDS) is associated with increased morbidity and mortality in the elderly population (≥65 years of age). Additionally, age is widely reported as a risk factor for the development of ARDS. However, the underlying pathophysiological mechanisms behind the increased risk of developing, and increased severity of, ARDS in the elderly population are not fully understood. This is compounded by the significant heterogeneity observed in patients with ARDS. With an aging population worldwide, a better understanding of these mechanisms could facilitate the development of therapies to improve outcomes in this population. In this review, the current clinical evidence of age as a risk factor and prognostic indicator in ARDS and the potential underlying mechanisms that may contribute to these factors are outlined. In addition, research on age-dependent treatment options and biomarkers, as well as future prospects for targeting these underlying mechanisms, are discussed.